Menjadikan Anak Saleh Dari Orangtua Saleh - Fitri Rayani Siregar (IAIN Padangsidimpuan, 2020)
This article describes how to become a good parent for the children. Become a good parent need knowledge, it must search by theirself with reading book, following parenting class. In this writing the author share some reward from the god has already given for human. It called learning reward, consisten reward, direction reward, listening reward and the last effective listening. All the reward can be applied for educate in creating good children. The parents need patience to practice the five reward , the result from effort the parents for conduct all the reward is a good children or Saleh. They will grow up by creative, selfconfidence, good character and they have a good relationship with their parents. Their parents is their friend, it created strong good character and excellent generation. Be a good parent to create a good children.